SDF1 Gene Variation Is Associated with Circulating SDF1α Level and Endothelial Progenitor Cell Number–The Bruneck Study - Xiao, Qingzhong (Public Library of Science, 2008)
BACKGROUND: Stromal cell-derived factor-1 (SDF1) and its receptor CXC chemokine receptor 4 (CXCR4) play a critical role in progenitor cell homing, mobilization and differentiation. It would be interesting to assess the predictive value of SDF-1alpha level for EPC number, and to ascertain whether there is a relationship between SDF1 gene variation, plasma SDF-1alpha level, and the number and function of circulating EPCs. We also tested whether EPC number and function was related to CXCR4 gene variation. METHODOLOGY AND PRINCIPAL FINDINGS: We genotyped a cohort of individuals who participated in the Bruneck Study for single nucleotide polymorphisms (SNPs) in the SDF1 and CXCR4 genes, and measured blood SDF1α level as well as EPC number and function. SDF1α levels were correlated with age, gender, alcohol consumption, circulating reticulocyte numbers, and concentrations of matrix metalloproteinase-9, C-reactive protein, cystatin C, fibrinogen and homocytein. In blood samples taken in 2005, EPC number was inversely associated with SDF1α level (p<0.001). EPC number in 2005 was also inversely associated with SDF1α level in 2000 (p = 0.009), suggesting a predictive value of plasma SDF1α level for EPC number. There was an association between the SDF1 gene rs2297630 SNP A/A genotype, increased SDF1α level (p = 0.002) and lower EPC number (p = 0.006). CONCLUSIONS: Our data indicate that a SDF1 gene variation (rs2297630) has an influence on SDF1α level and circulating EPC number, and that plasma SDF1α level is a predictor of EPC number.